การเปรียบเทียบคุณภาพของวิธีการวัดคะแนนพัฒนาการโดยใช้โมเดลโค้งพัฒนาการที่มีตัวแปรแฝงเป็นเกณฑ์ : การศึกษาแบบมอนติคาร์โล - นิอร ไชยพรพัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purposes of this research were to compare the quality of the three measuring growth methods based on the classical test theory which were 1) observed different score method (DS), 2) relative gain score (RG), and 3) balanced relative gain score (BRG) using the latent growth curve model as the criterion for the data that had changed in linear and nonlinear growth model and had different time-point-measurement. The 108 situations were built up by monte carlo technique using MPLUS version 4.1 from 4 conditions which were 1) form of data-changing, 2) time-point-measurement, 3) mean of level (ML), and 4) mean of slope (MS). The data were analyzed in order to estimate growth scores, and the scores quality using criterion-related validity and measurement error were compared by Hotelling test and scatter plot. The research results indicated that: 1) The growth scores from all of the three measuring growth methods had high level in criterion-related validity and low measurement errors. 2) For the data that had changed in linear growth model and basis coefficient is [0, 1, 2, 3, 4], it showed that the method of RG had better quality than DS and BRG, respectively. Even if in the different time-point-measurement condition. 3) For the data that had changed in linear growth model with basis coefficient [0, 0.2, 0.4, 0.6, 0.8], it showed that the method of RG had better quality then BRG and DS, respectively. It still had a better quality for 3 or 4 time-point-measurement conditions. But whenever the data had 5 time-point-measurement, the method of BRG had better quality than others. 4) For the data that had changed in nonlinear growth model, it showed that the method of RG had better quality than BRG and DS, respectively. It still had a better quality for 5 time-point-measurement conditions. But whenever the data had 3 or 4 time-point-measurement. The method of BRG had better quality than others.